The Value Of Fanily Life in the Film A Million Darling For Him (Jhon Fiske Semiotic Analysis) - Rizki Muhammad Akbar (GAYAKU PUBLISHER, 2023)
The family is the first and foremost place for the growth and development of children. If the atmosphere in the family is good and fun, then the child will grow well too. Otherwise it will hinder the growth of the child. The role of parents in the family is very important. Fathers tend to be in the public sector (earning a living). It is widely developed in society that single parent men cannot take care of their children properly and because they are busy making a living for their children, this research is entitled